APLIKASI MONITORING PENERIMA BEASISWA BIDIKMISI BERBASIS WEB, ANDROID DAN SMS GATEWAY - Helna Wardhana; Baiq Dinda Uswatun Hasanah (Universitas Bumigora, 2016)
Scholarships Bidikmisi (Education Support Student Achievement) is a tuition assistance is only intended for prospective students disadvantaged (poor). Bidikmisi scholarship program's mission is to revive hope for the poor and have adequate academic potential. STMIK Bumigora Mataram monitoring of scholarship recipients Bidikmisi still manually.Student party still controlling the GPA through the academic part and the difficulty in controlling the GPA scholarship recipients. The scholarship recipients and parents do not get information on the disbursement of funds led to lack of openness between students and parents. The solution of the existing problems is made Scholarship Bidikmisi Monitoring System Based Web, Android and SMS gateway. Through the website of the student can control GPA scholarship students each semester. Android applications can facilitate the control of student scholarship students only through mobile android, and with the SMS Gateway facilitate scholarship students and parents to get information on the disbursement of the funds.The conclusions obtained from this study is that the monitoring system can provide convenience for the student in control of the grantee Bidikmisi. This can be evidenced by the respondents who answered disagree as much as 75% and as much as 25% who answered strongly agree.